Edukasi Pentingnya Pemberian ASI Eksklusif pada Masyarakat Desa Allang Asaude - Laury Marcia Ch. Huwae; Kezia Cornelia Klau; Pretty Mitra Kristina Zebua; Inri Chartini Johansz; Kezia Sovici Tuhuleruw; Evanthely N. Ch. M. Tahalele; Joshua Amstrong Leuwol; Gladys R. Pamesti; Laura Bianca Sylvia Huwae; Johan Bruiyf Bension; Ronald Darlly Hukubun (Jurnal Pengabdian Masyarakat Waradin, 2025)
The First 1000 Days of Life (HPK) period is a crucial time that greatly influences a child's physical and cognitive development. During this period, fulfilling nutritional needs, especially through exclusive breastfeeding and appropriate complementary feeding, is very important. This community service activity aims to improve mothers' understanding of the importance of exclusive breastfeeding for mothers and babies. This community service activity was carried out by providing education to 12 breastfeeding mothers at the Sinar Kasih Integrated Health Post, Allang Asaude Village, Waesala Health Center area, Huamual District, West Seram Regency, through the distribution of leaflets and interactive question and answer sessions. The results showed that this activity succeeded in improving the understanding of the counseling participants about the benefits of exclusive breastfeeding for babies and mothers. This education is expected to encourage better exclusive breastfeeding practices, which will have a positive impact on children's health in the future.